Treatment Dilemma of Latrogenic Pseudoaneurysm of the Intracavernous Internal Carotid Artery in Young Girl Following Transnasal Transsphenoidal Surgery: A Case Report - Sharma, Amit K.; Jagetia, Anita; Singhal, Ghanshyam D; Bodeliwala, Shaam; Srivastava, Arvind K.; Singh, Daljit (Asian Journal of Neurosurgery, 2022)
Epistaxis following transnasal transsphenoidal (TNTS) removal of pituitary adenoma can be massive and life-threatening. The intracranial source of bleeding is usually the intracavernous segment of the internal carotid artery (ICA) or adjacent branches. Injury to the cavernous ICA can lead to pseudoaneurysm (PA) or fistula formation. Management of PA is different from saccular aneurysms. A timely diagnosis and adequate management can restore vessel integrity and prevent associated morbidity. A young patient of growth hormone-secreting pituitary adenoma, who underwent microscopic TNTS excision of the tumour, presented with massive epistaxis. Pseudoaneurysm of the cavernous ICA was initially not seen on computed tomography angiography and was later diagnosed on digital subtraction angiography. The attempted management of PA with coils without stent could not stop aneurysm recurrence. The management of such complicated PAs is discussed, and a literature review is done regarding epistaxis in growth hormone secreting adenoma.